AN ANALYSIS OF TRANSLATION TECHNIQUES AND QUALITY IN TERMS OF ACCURACY, ACCEPTABILITY AND READBILITY OF PI'S EXPRESSIVE SPEECH ACT IN THE FILM ENTITLED LIFE OF PI - Vibry Andina Nurhidayah (Universitas Sebelas Maret, 2013)
This research was conducted to analysis the translation techniques and quality of types on expressive speech acts exploited by Pi, the main character in the film “Life of PI”. The research used the Pragmatics approach with speech act as the field of study. It was a descriptive qualitative research and it employed purposive sampling as the sampling technique. The data in this research were the types of expressive speech acts. From the result of data analysis, there are four types of expressive speech acts employed by Pi character in the film “Life of PI”, they are thanking, apologizing, blaming and praising. From the analysis, the first finding of the research shows that the total data of research are 24 data. There are four expressive, thanking expressive speech act 7 data, apologizing speech act 10 data, blaming 3 data, and praising 4 data. The second finding of the research shows that there are two techniques employed by the translator in translating expressive speech act in the film “Life of Pi”. They are literal translation 19 data and explicit translation 5 data. The third finding dealing with the quality of translation, the translation of expressive speech act in the subtitle film “Life of Pi” belongs to accurate and acceptable and readable translation. For the accuracy of the translation, from 24 data, 19 data are accurately translated, 5 data are less accurately translated. For the acceptability of the translation, from 24 data, 21 data are acceptably translated, 3 data are less acceptably translated. For the readability, all the 24 data are readable.